Empowering Sustainable Mining for Green Intellectual Capital: The Mediating Influence of The Capital Human Organizational Index - Susanto, Andi Heru (Universitas Tanjungpura, 2026)
This research explores the strategic role of Human Resource Management in enhancing environmental performance through the mediation of the Capital Human Organizational Index (CHOI). Amidst regulatory pressures in the extractive industry, this study examines how financial capacity and organizational scale are transformed into ecological success by strengthening intellectual capital. Using purposive sampling, 40 mining companies listed on the Indonesia Stock Exchange (2018-2024) were analyzed, totaling 280 panel data observations. The analysis employed panel data regression with a Fixed Effect model and Sobel test via EViews 13. Findings reveal that profitability (ROE) cannot directly drive environmental improvement, indicating the limitations of financial resources without human capability support. However, firm size significantly triggers CHOI investment, which subsequently impacts PROPER ratings. Sobel test results confirm CHOI’s role as a key mediator, proving that employee competency development through green training is an essential managerial instrument for transforming structural assets into sustainable mining innovations. This study recommends that HR practitioners treat training costs as intangible asset investments rather than expenses, as they determine the company’s future environmental legitimacy and reputation.